How is fatalistic determinism linked to depression? The mediating role of self-control and resilience. (October 2021) - Fu, Jiawei; Zhao, Yajun; Feng, Xingwang; Wang, Yueru; Yu, Zongren; Hua, Liyun; Wang, Song; Li, Jingguang
Abstract: Previous studies have indicated that individuals who believe fatalistic determinism are more depressed than other individuals. In this study, by testing the mediating roles of self-control and resilience, we aimed to investigate how fatalistic determinism is linked to depression. One sample of high school students (Study 1, N  = 714) and another independent sample of college students (Study 2, N  = 1569) in China completed questionnaires about fatalistic determinism, depression, self-control, and resilience. Mediation analyses were conducted with fatalistic determinism as a predictor variable, self-control and resilience as mediators, and depression as an outcome variable. In both studies, we observed a replicable pattern of results. Fatalistic determinism was positively correlated with depression. Self-control and resilience played multiple mediating roles in the association between fatalistic determinism and depression through three mediating pathways: via self-control alone, via resilience alone, and via the effect of self-control on resilience. Together, the total mediation effect accounted for approximately half of the total effect (46.2% in Study 1 and 48.5% in Study 2). In conclusion, fatalistic determinism may increase the risk of developing depression either by simultaneously decreasing self-control and resilience (parallel mediation) or by decreasing resilience via reduced self-control (serial mediation). Highlights: Fatalistic determinism was positively associated with depression. Fatalistic determinism influenced depression by simultaneously decreasing self-control and resilience. Self-control and resilience sequentially mediated the link between fatalistic determinism and depression.